Determinants of Nam8-dependent splicing of meiotic pre-mRNAs - Qiu, Zhicheng R. (Oxford University Press, 2011)
Nam8, a component of yeast U1 snRNP, is optional for mitotic growth but required during meiosis, because Nam8 collaborates with Mer1 to promote splicing of essential meiotic mRNAs AMA1, MER2 and MER3. Here, we identify SPO22 and PCH2 as novel targets of Nam8-dependent meiotic splicing. Whereas SPO22 splicing is co-dependent on Mer1, PCH2 is not. The SPO22 intron has a non-consensus 5′ splice site (5′SS) that dictates its Nam8/Mer1-dependence. SPO22 splicing relies on Mer1 recognition, via its KH domain, of an intronic enhancer 5′-AYACCCUY. Mutagenesis of KH and the enhancer highlights Arg214 and Gln243 and the CCC triplet as essential for Mer1 activity. The Nam8-dependent PCH2 pre-mRNA has a consensus 5′SS and lacks a Mer1 enhancer. For PCH2, a long 5′ exon and a non-consensus intron branchpoint dictate Nam8-dependence. Our results implicate Nam8 in two distinct meiotic splicing regulons. Nam8 is composed of three RRM domains, flanked by N-terminal leader and C-terminal tail segments. The leader, tail and RRM1 are dispensable for splicing meiotic targets and unnecessary for vegetative Nam8 function in multiple synthetic lethal genetic backgrounds. Nam8 activity is enfeebled by alanine mutations in the putative RNA binding sites of the RRM2 and RRM3 domains.